Burden, professional support, and social network in families of children and young adults with muscular dystrophies. Issue 1 (22nd April 2015) - Magliano, Lorenza; Patalano, Melania; Sagliocchi, Alessandra; Scutifero, Marianna; Zaccaro, Antonella; D'angelo, Maria Grazia; Civati, Federica; Brighina, Erika; Vita, Giuseppe; Vita, Gian Luca; Messina, Sonia; Sframeli, Maria; et al.
ABSTRACT Introduction: This study explores burden and social and professional support in families of young patients with muscular dystrophies (MDs) in Italy. Methods: The study was carried out on 502 key relatives of 4‐ to 25‐year‐old patients suffering from Duchenne, Becker, or Limb‐Girdle MD who were living with at least 1 adult relative. Results: A total of 77.1% of relatives reported feelings of loss, 74.0% had feelings of sadness, and 59.1% had constraints in leisure activities. Burden was higher among relatives of patients with higher disability and who spent more daily hours in caregiving. Practical difficulties were higher among relatives who perceived lower help in patient emergencies and less practical support by their social network. Psychological burden was higher in those relatives who were unemployed, those with poorer support in emergencies, and those with lower social contacts. Conclusions: Caring for patients with MDs may be demanding for relatives even in the early stages of these disorders, especially when social support is poor and the patient's disability increases. Muscle Nerve52: 13–21, 2015